Peningkatan Kapabilitas Pengelolaan Kearsipan Pemerintahan Kampung Mukim Singkir Yan Kedah Malaysia - Andriyus, Andriyus; Herawaty, Yulia; Said, Mohd Syahril; Safitri, Bella Hidiyan (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
Archives are records or records of all activities carried out by both organisations and individuals, archives are a very important source of information in an activity or activity in the form of a collection of documents or records to provide information about a place. Meanwhile, archiving is a storage process in the form of materials or records systematically. Archives are closely related to correspondence activities, both in government agencies. Archival management is an important part of running the wheels of the organisation, archives are a source of information and the centre of the organisation's memory, archival management problems occur in various organisations, including the government. Archives are the identity of a government organisation, therefore the ability to manage archives is needed by government agencies. The purpose of this service activity is to improve the management capability of government archives so that they are well organised according to the principles of archival management and make it easier to find them when needed again. This activity was carried out by providing counselling on government archives management using lecture and discussion methods attended by government officials of Kampung Mukim Singkir Yan Kedah Malaysia. The results of the service showed that the service participants had very high enthusiasm in participating in the service carried out, this could be seen from the active participants in the discussion and question and answer sessions. From the results of monitoring and evaluation carried out both by using a partner satisfaction questionnaire and from direct communication with participants, they were greatly helped by these activities because they needed information about government archive management.Arsip merupakan catatan atau rekaman semua kegiatan baik yang dilakukan oleh organisasi maupun orang perorangan, arsip adalah sumber informasi yang sangat penting dalam sebuah kegiatan atau aktivitas yang berupa kumpulan dokumen atau warkat untuk memberikan informasi mengenai suatu tempat. Sedangkan kearsipan adalah suatu proses penyimpanan yang berupa bahan- bahan atau warkat secara sistematis. Kearsipan erat hubungannya dengan kegiatan surat menyurat, baik di instansi pemerintah. Pengelolaan kearsipan merupakan bagian penting dalam menjalankan roda organisasi, arsip merupakan sumber informasi dan pusat ingatan organisasi, permasalahan pengelolaan kearsipan terjadi diberbagai organisasi tidak terkecuali pada pemerintahan. Arsip merupakan jati diri suatu organisasi pemerintah oleh karena itu dibutuhkan kemampuan pengelolaan kearsipan oleh lembaga pemerintah. Tujuan kegiatan pengabdian ini adalah untuk meningkatkan kapabilitas pengelolaan kearsipan pemerintahan supaya tertata dengan baik sesuai prinsip-prinsip manajemen kearsipan serta memudahkan untuk menemukannya ketika dibutuhkan kembali. Kegiatan ini dilakukan dengan cara memberikan penyuluhan tentang pengelolaan kearsipan pemerintahan dengan metode ceramah dan diskusi yang dihadiri oleh perangkat pemerintah Kampung Mukim Singkir Yan Kedah Malaysia. Hasil pengabdian menunjukkan bahwa peserta pengabdian memiliki antusias yang sangat tinggi dalam mengikuti pengabdian yang dilakukan hal ini terlihat dari aktifnya peserta dalam sesi diskusi dan tanya jawab. Dari hasil monitoring dan evaluasi yang dilakukan baik dengan menggunakan angket kepuasan mitra maupun dari komunikasi langsung dengan peserta mereka sangat terbantu dengan kegiatan tersebut karena mereka membutuhkan informasi tentang pengelolaan kearsipan pemerintahan.